Approved budget for 1993 : Osun state of Nigeria: including budget speech - Federal ministry of finance (Lagos, Nigeria : TAA Printing & Publishing Company, 1993)
The book is the 1993 approved budget of Foundation Budget presented by His Excellency, Alhaji Isiaka Adetunji Adeleke, the Executive Governor of Osun State.
Osun State of Nigeria: Estimates 1993 including budget speech
osa 02/04/19
Loans
Keywords: Budget; Fiscal; Nigeria